The digestion of thorium cake in nitric acid - Songip, Ahmad Rahman; Meor Sulaiman, Meor Yusof (1989)
Radioactive thorium cake is produced as a waste from the monazite processing plant in Malaysia. Strategic nuclear fuel elements such as thorium and uranium can be extracted from this waste. It was found that the waste contains up to 33% and 1.4% of ThO2 and U3O8 respectively. Digestion is the first step in this extractive mettalurgy process. Laboratory studies have been conducted to obtain optimum conditions for extracting thorium and uranium from the waste. Experiments were carried out by using nitric acid because of its good recovery for these elements and it also acts as the salting agent for tri-butyl-phosphate in the subsequent liquid-liquid extraction stage. The extraction was found to be sensitive to the concentration of nitric acid. The major dissolution of both elements was obtained at an acid concentration range of 60-80%, percentage of pulp density of 40% and temperature of 70C.